The effect of functional insulin therapy on glycaemic parameters in children with diabetes mellitus type 1 - Diana Štimjanin-Koldžo; Salem Alajbegović; Ena Štimjanin; Jasmina Mehinagić (Medicinski glasnik, 2017)
Aim: The aim of the study is to evaluate the effect of a prospectively conducted interactive 5-day education programme based on Düsseldorf model on glycated haemoglobin (A1C), and total daily dose of insulin in type 1 diabetes patients. Methods: A total of 67 type 1 diabetes patients was analysed; mean age of 11±0.68 years, 43 females and 24 males. The programme was led by a trained team of diabetes specialist doctors and nurses. All subjects and their parents completed a knowledge test about diabetes at beginning, and at the end of education, and after 12 months (30 questions). Subjects were evaluated for total daily insulin, and HbA1c at baseline, as well as 3, 6, 9 and 12 months after the end of the education programme. Results: Results: of the knowledge test after the education have shown higher knowledge at baseline. At the end of the education programme an average of total daily insulin dose was significantly lower. There was a 3.17% reduction in HbA1c values over 9 months, and 1.8% over 12 months in the comparison to the baseline values (p<0.001). Conclusions: Structured education programme of functional insulin therapy was associated with improved glycaemic control in type 1 diabetes patients and their parents. It motivated patients and parents to improve glycaemic control. One year after the follow up, glycaemic control was worsening, due to lack of patients' motivation, therefore, there is a need for yearly re-education.
Keywords: child; parents; education of diabetes; functional insulin therapy; glycaemic control